THE EFFECT OF EARNINGS PERSISTENCE AND EARNINGS TRANSPARENCY ON COMPANY PERFORMANCE WITH CORPORATE GOVERNANCE AS MODERATING VARIABLE (Empirical Study in Manufacturing Company that Listed in Indonesia Stock Exchange in 2014-2016) - Melinda Malau (EAJ (Economic and Accounting Journal), 2019)
ABSTRACTEarnings persistence and earnings transparency are an important factors in company performance. The quality of financial statement will differentiate performance between one company to another. The research purposed to analyze the effect of earnings persistence and earnings transparency on the company performance. In addition, the research purposed to analyze corporate governance as a moderating variable can strengthens the effect between earnings persistence and earnings transparency on company performance. This research using sample of 363 firms-year in 2014-2016 and applying panel data analysis. The results show that earnings persistence variable has a positive significant effect on the company performance. Earning transparency also has a positive significant effect on company performance. For corporate governance as a moderation variable strengthens the effect between earnings persistence and earning transparency to the company performance. Size and age also have a positive significant effect on company performance. Keywords: earnings persistence; earnings transparency; company performance; corporate governance.